An examination of the Pre-Dorset caribou hunters from the deep interior of Southern Baffin Island, Nunavut, Canada - McAvoy, Deanna Grace (2014)
The faunal remains from four archaeological sites on the northwest shore of Mingo Lake, in the interior of Southern Baffin Island, are examined in this thesis. All four sites are radiocarbon dated to Pre-Dorset times (4500 – 2700 BP). The faunal assemblage is dominated by caribou remains. As such, this study is the first, large-scale faunal analysis of an interior Pre-Dorset site with caribou as a main subsistence resource. In total 18,710 faunal bones were examined. Elemental frequencies, fracture patterns, bone burning, and butchering patterns will provide important insights into the lifeway of the Pre-Dorset. The results of the thesis indicate that the Pre-Dorset were utilizing the Mingo Lake area during the late summer into early fall. The main activity at all four sites was caribou hunting with a focus on marrow extraction. The sites served dual purposes as habitation and butchering sites and were occupied for varying lengths of time. May 2014